2015
DOI: 10.6000/1929-6029.2015.04.01.16
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Risk Factors for Breast Cancer in a Primary Oncology Clinic in Benghazi-Libya

Abstract: Introduction: Libya is a North African country classified under the Eastern Mediterranean Regional Office. In response to the general paucity of literature regarding cancer in Libya, this study aims to analyze various risk factors for breast cancer among patients in Benghazi, Libya. Material and Methods: Using records from a major primary oncology clinic, data was gathered from breast cancer patients. A total of 301 patients were diagnosed with breast cancer in the study period. For the purpose of risk factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…The occurrence of breast cancer in our study is strongly associated with young age with nearly 73% of cases arising in individuals who are 50 years or younger, in concordance with other reported study [14]. The mean age of disease get diagnosed was about 47.72, is similar to other studies [14,15,16]. In the recent study invasive ductal carcinoma NST is the commonest histological type of breast carcinoma accounting 95.9% of the total cases, in concordance with other reports [16, 17, 18, 19, 20 & 21] and also consistent with other study showed that, the commonest histological types of the breast cancer cases in Libya, Nigeria and Finland, was non-specific variety of invasive ductal carcinoma [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The occurrence of breast cancer in our study is strongly associated with young age with nearly 73% of cases arising in individuals who are 50 years or younger, in concordance with other reported study [14]. The mean age of disease get diagnosed was about 47.72, is similar to other studies [14,15,16]. In the recent study invasive ductal carcinoma NST is the commonest histological type of breast carcinoma accounting 95.9% of the total cases, in concordance with other reports [16, 17, 18, 19, 20 & 21] and also consistent with other study showed that, the commonest histological types of the breast cancer cases in Libya, Nigeria and Finland, was non-specific variety of invasive ductal carcinoma [14].…”
Section: Discussionsupporting
confidence: 92%
“…A study observed that, the majority of (44.1%) cases with T2 stage that correlate with our results [8]. Interestingly, another performed study showed over 90% of breast cancer patients are diagnosed at stage II or later [15]. Similarly, other studies also observed highest frequency of tumors with T2 stage [24, 25 & 26].…”
Section: Discussionsupporting
confidence: 90%